PROYEKSI PERTUMBUHAN PENDUDUK TERHADAP KETERSEDIAAN FASILITAS KESEHATAN DI KECAMATAN KOTO TANGAH KOTA PADANG - Pasaribu, Maria Rosaria; Syahar, Fitriana (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
This research aims to (1) analyze the population growth rate and the availability of health facilities in Koto Tangah in 2020 (2) projecting the population and the need for health facilities in Koto Tangah in 2030 (3) analyze the reach of health facilities to residential areas in Koto Tangah in accordance with Indonesian National Standards. This research used descriptive quantitative method. The data analysis techniques used are population growth rate analysis, analysis of the availability and needs of health facilities using the Indonesian National Standard, to calculate population projections using geometric formulas, and spatial analysis, namely buffering techniques using Geographic Information System (GIS) software.. Based on the research result of the research found that (1) The availability of health facilities in Koto Tangah, namely polyclinics, has not been fully met based on the Indonesian National Standard and health facilities for health centers and pharmacies have been met based on the Indonesian National Standard (2) The projection of the need for health facilities in Koto Tangah in 2030 shows the need for a lot of additional health facilities of 91 units (3) For the radius of coverage of health facilities of puskesmas, polyclinics, and pharmacies, some of which are not yet able to reach the entire settlement in Koto Tangah. Keyword : Projection, Population growth, Health Facilities, Range